Simulador PhET para el aprendizaje del movimiento rectilíneo uniforme, carrera de Pedagogía de las Ciencias Experimentales Matemáticas y la Física - Paguay Maji, Bryan Alexis (2024)
The study of kinematics proves to be complex to learn in today's society due to the current trend of being more technology-oriented rather than being immersed in a classroom. That's why teachers tirelessly strive to innovate by using educational resources to maintain an efficient student-teacher connection. Therefore, this research aimed to use the PhET simulator for learning Uniform Rectilinear Motion, a topic within kinematics, among first-semester students in the Pedagogy of Experimental Mathematical Sciences and Physics program at the National University of Chimborazo. A quasi-experimental design with a quantitative approach and an explanatory research level was employed to relate two variables. The sample consisted of 25 students for the control group and 24 for the quasi-experimental group. Data collection involved pre-tests and post-tests, with the final group undergoing treatment to demonstrate the significant impact of using the simulator. Data processing was carried out using Microsoft Excel, and hypothesis testing was performed using SPSS software. It was concluded that students receiving traditional classes solely using the blackboard tend to have low academic performance, as evidenced by the mean obtained in the control group, which is 4. When using the PhET simulator, a significant impact is observed, allowing for a better understanding of both theoretical and practical content, with an average score of 7.5, thereby improving the teaching-learning process